2018
DOI: 10.1590/1413-70542018426022318
|View full text |Cite
|
Sign up to set email alerts
|

Production and mechanical evaluation of biodegradable composites by white rot fungi

Abstract: The production of plastic packing grows worldwide, resulting in the accumulation of these materials in the environment due to improper disposal and problems related to degradation. Alternatively, composites produced with agricultural residues and filamentous fungi may exhibit physical and mechanical properties similar to or greater than expanded polystyrene, depending on the fungal species and substrate of the cultivation. In the literature, no reports were found on the use of coconut powder and edible fungi o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 30 publications
0
17
0
2
Order By: Relevance
“…However, the increase in the cultivation period from 30 to 45 days of complete colonization may have resulted in reduced nutrient availability for microbial metabolism, and in the lower mass loss of the composite colonized by LED CHI and LED 96/18, when compared to 30 days. Teixeira et al (2018) observed a composite mass loss of 72.4%, on average with the isolates of P. sanguineus, Pleurotus spp. cultivated also in coconut powder-based substrate with wheat bran, which represents greater mass loss than that of composites colonized by L. edodes, probably due to the higher rate of degradation of the composite by the isolates tested by Teixeira et al (2018).…”
Section: Mechanical Strength Of Shiitake Mushroom Compositementioning
confidence: 95%
See 4 more Smart Citations
“…However, the increase in the cultivation period from 30 to 45 days of complete colonization may have resulted in reduced nutrient availability for microbial metabolism, and in the lower mass loss of the composite colonized by LED CHI and LED 96/18, when compared to 30 days. Teixeira et al (2018) observed a composite mass loss of 72.4%, on average with the isolates of P. sanguineus, Pleurotus spp. cultivated also in coconut powder-based substrate with wheat bran, which represents greater mass loss than that of composites colonized by L. edodes, probably due to the higher rate of degradation of the composite by the isolates tested by Teixeira et al (2018).…”
Section: Mechanical Strength Of Shiitake Mushroom Compositementioning
confidence: 95%
“…Teixeira et al (2018) observed a composite mass loss of 72.4%, on average with the isolates of P. sanguineus, Pleurotus spp. cultivated also in coconut powder-based substrate with wheat bran, which represents greater mass loss than that of composites colonized by L. edodes, probably due to the higher rate of degradation of the composite by the isolates tested by Teixeira et al (2018).…”
Section: Mechanical Strength Of Shiitake Mushroom Compositementioning
confidence: 95%
See 3 more Smart Citations